PKA plays a conserved role in regulating gene expression and metabolic adaptation by phosphorylating Rpd3/HDAC1 - Wenjing Dai; Qi Yu; Rui Ma; Zhu Zheng; Lingling Hong; Yuqing Qi; Fei He; Min Wang; Feng Ge; Xilan Yu; Shanshan Li (Nature Communications)
Abstract Cells need to reprogram their metabolism to adapt to extracellular nutrient changes. The yeast histone acetyltransferase SAGA (Spt-Ada-Gcn5-acetyltransferase) has been reported to acetylate its subunit Ada3 and form homo-dimers to enhance its ability to acetylate nucleosomes and facilitate metabolic gene transcription. How cells transduce extracellular nutrient changes to SAGA structure and function changes remains unclear. Here, we found that SAGA is deacetylated by Rpd3L complex and uncover how its deacetylase activity is repressed by nutrient sensor protein kinase A (PKA). When sucrose is used as the sole carbon source, PKA catalytic subunit Tpk2 is activated, which phosphorylates Rpd3L catalytic subunit Rpd3 to inhibit its ability to deacetylate Ada3. Moreover, Tpk2 phosphorylates Rpd3L subunit Ash1, which specifically reduces the interaction between Rpd3L and SAGA. By phosphorylating both Rpd3 and Ash1, Tpk2 inhibits Rpd3L-mediated Ada3 deacetylation, which promotes SAGA dimerization, nucleosome acetylation and transcription of genes involved in sucrose utilization and tricarboxylate (TCA) cycle, resulting in metabolic shift from glycolysis to TCA cycle. Most importantly, PKA phosphorylates HDAC1, the Rpd3 homolog in mammals to repress its deacetylase activity, promote TCA cycle gene transcription and facilitate cell growth. Our work hence reveals a conserved role of PKA in regulating Rpd3/HDAC1 and metabolic adaptation.